The role of dietary fibre and prebiotics in the paediatric diet. Issue 4 (10th June 2020) - Boctor, Dana
Abstract: Dietary fibres are resistant to digestion and absorption. Prebiotics are fermentable dietary fibres that confer health benefits through their effects on microbiome composition and activity. The range of physiological benefits from consuming dietary fibres is broad. Encouraging children to eat fibre-rich foods promotes a nutrient-dense diet. Introducing a variety of dietary fibre sources to young children helps establish future dietary choices and a more diverse intestinal microbiota. Low-fibre intake is associated with a higher prevalence of constipation and obesity.